THE SIGNIFICANCE OF TUTORING FOR THE FORMATION OF THE FUTURE TEACHER-STUDENTS’ VALUE BEHAVIOUR (EDUCATION IN THE 21ST CENTURY, 2023)
The most important tendency in the human society development in the 21st century is connected with the changes in the personality type, the human awareness of themselves as a life and culture value. That is why higher education should be value-oriented. And the goal of the pedagogical education should be the formation of the teachers’ value behaviour. Teachers’ value behaviour, undoubtedly, will help students in their value orientation in the world of various, sometimes controversial values, will raise the educators’ cultural and professional level, as well as the prestigiousness of their profession. The concept “Value Behaviour” has got different interpretations, but there is one common feature about them all, i.e. that the values manage human behaviour. The formation of the “value behaviour” takes place mainly during the educational process at higher school institution, while studying subjects of the psychological-pedagogical cycle. But the process becomes more focused through studying “Pedagogic Axiology”. During the formation of the value behaviour, the student as the subject of that process, needs assistance in the realization of the own axiological position, etc. To our mind, all these problems are successfully solved in case of tutoring the students.In the pedagogical literature, there are various definitions of the word “tutor”. We base upon the one which describes “tutor” as a pedagogue, who takes a tutorial position towards the student in order to develop subject – subject relationship between the participants of the educational process. The tutor’s activity content is defined by his functions. Carrying out the assigned tasks, the educator selects different forms of activity and pedagogical technologies. We have elaborated criteria for the selection of such technologies. They should raise the level of existential reflection, broaden the spectrum of social value conception, develop communicative competencies, etc. With the consideration of these criteria, the following technologies were applied during the experiments: organization of the research activity, dialogue interaction, critical thinking and others. The analysis of the results of various types of control over the students’ cognitive activity while studying “Pedagogic Axiology” during experimental work via tutoring displayed a much higher level than before the experiment.The results of the conducted research highlighted the fact that the formation of the future teachers’ value behaviour takes place more effectively via including “Pedagogic Axiology”, tutoring students, in the curriculum.
Keywords: values, value behaviour, Pedagogic Axiology, tutor, tutoring, pedagogic technologies